HISTORY | Ibans of S'wak: from warriors to nation builders - Malhi, Ranjit Singh (2025)
The Ibans, historically referred to as Sea Dayaks due to their past involvement in sea piracy, are the largest ethnic group in Sarawak, numbering approximately 750,000 - which is about 29 percent of the state’s population.